2017
DOI: 10.1111/ijfs.13400
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, functional, thermal and structural properties of isolated Kabuli chickpea proteins as affected by processing approaches

Abstract: Summary Kabuli chickpea seeds were processed by soaking only and soaking followed either by pressure cooking or roasting. Proteins were isolated from both raw and processed seeds, and the effects of these processing approaches on the physicochemical, functional, thermal and structural properties as well as SDS‐PAGE profiles of the protein isolates were investigated. Thermal processes significantly (P < 0.05) decreased protein yield, content, colour difference, emulsifying properties and protein solubility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 28 publications
6
35
0
Order By: Relevance
“…It was observed that isolated chickpea protein had Amide I band at 1642 and Amide II band at 1536. Additionally, peaks were found at 3300 representing OH stretching and 2950 corresponding CH stretching in FTIR spectra of protein isolate of chickpea . Interactions between phenolic compound and protein resulted shift of the Amides A and B peaks.…”
Section: Resultsmentioning
confidence: 94%
“…It was observed that isolated chickpea protein had Amide I band at 1642 and Amide II band at 1536. Additionally, peaks were found at 3300 representing OH stretching and 2950 corresponding CH stretching in FTIR spectra of protein isolate of chickpea . Interactions between phenolic compound and protein resulted shift of the Amides A and B peaks.…”
Section: Resultsmentioning
confidence: 94%
“…The results could be explained by the fact that these two raw pulse flours had lower pasting temperatures and peak times and less pasting viscosities than the wheat flour control (Setia et al, ). The lower pasting viscosities of the flour blends could be partly explained by their smaller starch contents than the wheat flour control (Table ): Starch is known to be the primary component contributing to the viscosity development of flours during pasting (Kweon et al, ; Wani et al, ; Xu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Germination tends to enhance the emulsifying properties and foaming capacity of pulse flours (El-Adawy, Rahma, El-Bedawey, & El-Beltagy, 2003;Ghavidel & Prakash, 2006;Setia et al, 2019). This treatment also appears to be promising in increasing the digestibility of starch and protein, two major macronutrients in pulse flours (Ghavidel & Prakash, 2007;Setia et al, 2019;Xu et al, 2017). Furthermore, germination can noticeably reduce the strong and pungent flavor of pulse flours (Bellaio, Kappeler, Rosenfeld, & Jacobs, 2013;Roland et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of chickpea flour combined with other hydrocolloids has also been suggested to produce glutenfree bread and snacks (Rachwa-Rosiak et al, 2015;Herranz et al, 2016). Heat (Xu et al, 2017) and fermentation (Chandra-Hioe et al, 2016) were investigated as treatments to improve chickpea flour functionality. But all such treatments decreased emulsification and foaming ability compared to raw samples.…”
Section: Introductionmentioning
confidence: 99%